Estudo de cultivares de soja irrigada nas condições do semiárido - Albuquerque, José Ricardo Tavares de (2020)
Soybean [Glycine max (L.) Merrill] is the legume of greatest economic importance. The worldwide interest in the cultivation of this legume is due to the excellent combination presented in terms of yield and low production cost due to the high levels of protein (40%) and oil (20%) of the seeds, respectively. Brazil is the largest exporter and the second largest producer of oilseeds. However, in the semiarid region, soybeans are not yet sown, although some cultivars are rustic and can be adapted in this region. The identification of genotypes with high yield and grain stability in the cultivation conditions of the Brazilian semiarid, characterized by high temperatures and concentrated precipitation in a few months of the year, are extremely important. When genotypes are evaluated under different environmental conditions, their relative performance may be altered, leading to the phenomenon called genotype-environment interaction. In this sense, 21 soybean cultivars were evaluated in randomized blocks with four replications during the dry seasons of 2016-2017 and rainy seasons of 2017-2018 in Mossoró-RN, for oil content, yield and its components. Factor regression and principal component analysis methodologies were used with the predictions of the sum of the genotypic effects and the interaction to quantify the role of five environmental covariates on the genotype by environment interaction. The GGE Biplot and Harmonic Average of Relative Performance methodologies of Genotypic values were also used to identify adapted and stable genotypes. Precipitation, relative humidity and temperature contribute positively to increase the oil content while the minimum temperature and solar radiation, to reduce. The interaction between genotypes for years in soy has a strong influence on the environment, is predominantly quantitative and makes it difficult to recommend genotypes in the semiarid region. The most stable genotypes adapted to grain yield and oil content are BMX OPUS IPRO, Pampeana 007 RR, Pampeana 20 RR, BRS Sambaíba RR, P 98Y70 RR, BRS 333 RR, BRS 9280 RR, M 8644 IPRO, M 8372 IPRO and ST 920 RR